Experimental and numerical investigation on the novel latent heat exchanger with paraffin/expanded graphite composite. (5th November 2018) - Lin, Wenzhu; Wang, Qianhao; Fang, Xiaoming; Gao, Xuenong; Zhang, Zhengguo
Highlights: A novel latent heat exchanger with two flow channels was developed and tested. Experimental tests about charging and discharging performance of novel heat exchanger was presented. The detailed performance of phase change material was investigated numerically. Abstract: In this paper, a novel latent heat exchanger with two flow channels was investigated experimentally and numerically. The phase change material was filled in the annular tube, while the working fluid flow in the shell and tube side runner. The design of multi flow channels allow it apply into energy storage system with different working fluid. The paraffin/expanded graphite composite with phase changing temperature around 50 °C was filled in the annular tubes. Heating and discharging tests have been performed in different flow rate. The numerical model was built and validated with experimental data. The experimental results indicates that overall energy shows decreasing tendency with higher flow rate while the average power increases with inlet velocity. The liquid fraction and temperature distribution of PCM was studied numerically by validated simulation model. In addition, it can conclude that the heat resistance of system lay in the PCM side, the improvement of system overall thermal conductivity still need further investigation.